Unique Selling Points Influencing Event Venue Sales at Graha Sarina Vidi Yogyakarta - Yuniati, Nining; Sulasmi, Sri (CV. Ulil Albab Corp, 2025)
Unique Selling Points Influencing Event Venue Sales at Grha Sarina Vidi Yogyakarta. Event venue entrepreneurs or convention center owners need to understand what event organizers consider when choosing a venue. This research examines Innovation Capability, Price, and Venue Atmosphere as unique selling points that are indicated to influence event organizers in choosing a convention center. Based on regression testing conducted on clients who chose the Grha Sarina Vidi for 1 year (114 respondents), both organizers and individuals found that all three factors are indeed considered important factors that must be chosen as an event venue.